The posttranslational modification of tubulin undergoes a switch from detyrosination to acetylation as epithelial cells become polarized - Quinones, Geraldine B. (The American Society for Cell Biology, 2011)
Tubulin posttranslational modifications (PTMs) have been suggested to provide navigational cues for molecular motors to deliver cargo to spatially segregated subcellular domains, but the molecular details of this process remain unclear. Here we show that in Madin-Darby Canine Kidney (MDCK) epithelial cells, microtubules express several tubulin PTMs. These modifications, however, are not coordinated, and cells have multiple subpopulations of microtubules that are marked by different combinations of PTMs. Furthermore these subpopulations show differential sensitivity to both drug- and cold-induced depolymerization, suggesting that they are functionally different as well. The composition and distribution of modified microtubules change as cells undergo the morphogenesis associated with polarization. Two-dimensionally polarized spreading cells have more detyrosinated microtubules that are oriented toward the leading edge, but three-dimensionally polarized cells have more acetylated microtubules that are oriented toward the apical domain. These data suggest that the transition from 2D polarity to 3D polarity involves both a reorganization of the microtubule cytoskeleton and a change in tubulin PTMs. However, in both 2D polarized and 3D polarized cells, the modified microtubules are oriented to support vectorial cargo transport to areas of high need.